2020
DOI: 10.1152/ajpheart.00176.2020
|View full text |Cite
|
Sign up to set email alerts
|

The role of endothelial autocrine NRG1/ERBB4 signaling in cardiac remodeling

Abstract: Neuregulin-1 (NRG1) is a paracrine growth factor, secreted by cardiac endothelial cells (ECs) in conditions of cardiac overload/injury. The current concept is that the cardiac effects of NRG1 are mediated by activation of ERBB4/ERBB2 receptors on cardiomyocytes. However, recent studies have shown that paracrine effects of NRG1 on fibroblasts and macrophages are equally important. Here, we hypothesize that NRG1 autocrine signaling plays a role in cardiac remodeling. We generated EC-specific Erbb4 knock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 58 publications
0
15
0
Order By: Relevance
“…NRG1 is a member of the neuregulin family that interacts with the EGFR family and modulates the repair of neural damage as well as immune response in the nervous system ( Kataria et al, 2019 ). Apart from neural modulatory function, secretion of NRG1 from fibroblast and endothelial cells also participates in the fibrotic remodeling of myocardial cells ( Dugaucquier et al, 2020 ). Whole-genome sequence analysis has revealed the association between NRG1 and free thyroxine ( Taylor et al, 2015 ), while it has also been found to influence the predisposition to thyroid carcinoma ( He et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…NRG1 is a member of the neuregulin family that interacts with the EGFR family and modulates the repair of neural damage as well as immune response in the nervous system ( Kataria et al, 2019 ). Apart from neural modulatory function, secretion of NRG1 from fibroblast and endothelial cells also participates in the fibrotic remodeling of myocardial cells ( Dugaucquier et al, 2020 ). Whole-genome sequence analysis has revealed the association between NRG1 and free thyroxine ( Taylor et al, 2015 ), while it has also been found to influence the predisposition to thyroid carcinoma ( He et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…NRG1 ligand binding triggers homodimerization of ErbB4 and heterodimerization of ErbB2/3, ErbB2/4, ErbB3/4 ( Carraway and Cantley, 1994 ; Sweeney et al, 2001 ; Yarden and Sliwkowski, 2001 ), followed by downstream signaling through the central pathway ( Xu et al, 2010 ; Fernandez-Cuesta et al, 2014 ). In some studies, the NRG1-ErbB pathway is believed to be a compensatory protective mechanism for cardiac injury ( Bersell et al, 2009 ; Odiete et al, 2012 ; Dugaucquier et al, 2020 ). The NRG1-ErbB signaling axis is a critical mediator of cardiac development, and growing evidence supports a role for this system in the intricate cross-talk between the microvascular endothelium and myocytes in the adult heart.…”
Section: Nrg1 and Its Regulationmentioning
confidence: 99%
“…NRG1, which controls the formation of excitatory and inhibitory synapses in cortical circuits, is a schizophrenia risk gene [39], and is associated with multiple relapsing disorders. In addition, NRG1 plays an important role in parabens of fibroblasts and macrophages [40]. Overexpression of mutant PMP2 also leads to CMT1 phenotype [41], and aberrant AKT3 expression helps form M2 macrophage specificity [42].…”
Section: Agingmentioning
confidence: 99%